Unveiling the potential of acetic acid-based hydrophobic natural deep eutectic solvents for phytochemical extraction - Srivastava R.; Bhardwaj N.; Jain S.K.; Metya A.K.; Parambil J.V. (My University, 2025)
Solvent choices in medicinal plant research are driven by cost-effectiveness, minimal adverse effects, and selectivity towards specific bioactive compounds. Natural deep eutectic solvents (NADES) are a category of green and tunable solvents utilized for phytochemical extraction. However, it is challenging to effectively use many NADES in phytochemical extraction due to the difficulty of solvent recovery and high viscosity. This research depicts the development of two new hydrophobic polar and non-polar NADES (AT13 and AD12). Here, AT13 is comprised of acetic acid and thymol in a molar ratio of 1:3, while AD12 is composed of acetic acid and n-decanoic acid in a molar ratio of 1:2. The physicochemical and structural characteristics of AT13 and AD12 were investigated using experimental and simulation techniques. AD12 has polarity similar to chloroform, whereas AT13 has polarity between water and methanol. Their lower viscosity and density compared to several known NADESs make them favorable solvents for phytochemical extraction. Moreover, their hydrophobic nature makes them easily recoverable and reusable NADES after phytochemical extraction. An extraction study from Aegle marmelos leaves revealed that AT13 and AD12 are more efficient than ethanol in extracting specific phytochemicals. AD12 is preferred for extracting aegeline, whereas AT13 is an effective extractive solvent for scopoletin. Additionally, both AD12 and AT13 are suitable to extract rutin. Furthermore, hydrophobic constituents of AT13 and AD12 were recoverable and reusable after extraction. Thus, the research presented here enhances the sustainability and efficacy of solvents used in phytochemical extraction. © 2024 Elsevier B.V.